Identifikasi Bakteriologis Jamu Kunyit Asam Yang Dijual di Wilayah Kelurahan Sesetan Kecamatan Denpasar Selatan - Arjani, Ida Ayu Made Sri; Wardani, Ni Luh Ayu Desy; Suryaningsih, Putu Ayu; Hadi, Muhammad Choirul (Poltekkes Kemenkes Denpasar, 2023)
Herbal turmeric tamarind is a traditional drink that has many health benefits for the body, it is made from herbal ingredients such as turmeric, tamarind fruit, granulated sugar/jaggery, lime juice, and can also be added with betel nut extract. The manufacture of tamarind and turmeric herbs is still very simple, so it is susceptible to contamination by bacteria that can cause health problems. The purpose of this study was to determine the bacteriological description of tamarind and turmeric herbs sold in the Sesetan Village, South Denpasar District. The parameter analyzed is the Total Plate Number. This study used a descriptive quantitative design by conducting laboratory tests. The sample size is 15 samples of tamarind turmeric herb with saturated sampling technique. The results showed that 13 samples (86.7%) meet the standard and 2 samples (13.3%) did not meet the total plate number standard according to the Regulation of the Food and Drug Supervisory Agency of the Republic of Indonesia Number 12 of 2014. It can be concluded that the bacteriological quality of herbal medicine of the tamarind turmeric meets the standards so that the seller must pay attention to the quality of the tamarind turmeric herbal medicine.